Socioeconomic dilemmas of commercial markets for invasive species: lessons from lionfish in Mexico. (9th December 2022) - Quintana, Anastasia; Marcos, Sergio; Malpica-Cruz, Luis; Tamayo, Lizbeth; Canto Noh, José Ángel; Fernández-Rivera Melo, Francisco; Fulton, Stuart
Abstract: "If you can't beat 'em, eat 'em": the development of commercial markets is an emerging strategy to control invasive species. This strategy may have fewer unintended ecological impacts than genetic modification and biological control; however, its unintended social impacts are poorly understood. We discuss the social dilemmas and opportunities created by commercializing invasive species, based on the experiences of fishing cooperatives' harvest of invasive lionfish ( Pterois sp.) in the Mexican Caribbean. In Cozumel, Mexico, a pilot commercial fishery began in 2012, and by 2015 had seemingly succeeded at reducing local lionfish abundance. However, three social dilemmas have accompanied this process. First, though designed to support sustainability, this market disproportionately benefits fishers that use fishing gear considered "unsustainable". Second, this strategy reinforces the narrative of fishers trapped in a "tragedy of the commons, " while simultaneously depending on the fishers' participation. Finally, the programme's very success has led to its own demise, disproportionately affecting the programme's most invested participants. These and similar dilemmas may be inevitable when systems in place for sustainable resource harvest are repurposed for resource collapse. However, fishing cooperatives have managed to navigate these dilemmas in partnership with governmental and non-governmental organization (NGO) advocates to position themselves as conservation leaders.